2000
DOI: 10.1034/j.1600-0609.2000.065005322.x
|View full text |Cite
|
Sign up to set email alerts
|

Defective platelet aggregation in polycythaemia vera is not caused by impaired calcium signaling, phospholipase D activation or decreased amounts of focal adhesion proteins

Abstract: We have previously demonstrated that platelets in polycythaemia vera (PV) exhibit decreased aggregation after stimulation with platelet activating factor (PAF) and reduced expression of GPIIIa on both resting and stimulated platelets. In the present study, we investigated if these results were related to changes in the mobilization of intracellular calcium, activation of phospholipase D (PLD) or amounts of GPIIIa and the intracellular tyrosine kinases Fak, Syk, Grb2, Shc and rhoA. Intracellular calcium levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Moliterno et al (1998 ) demonstrated that TPO stimulation of PV platelets conferred an impaired tyrosine phosphorylation of proteins with molecular masses of 125, 95 and 85 kDa. In contrast, thrombin induced similar phosphorylation patterns to those in controls, a finding that we have also made ( Le Blanc & Samuelsson, 1998). Furthermore, phosphorylation of JAK‐2 and its substrate STAT‐5 was also diminished in all patients that they investigated ( Moliterno et al , 1998 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moliterno et al (1998 ) demonstrated that TPO stimulation of PV platelets conferred an impaired tyrosine phosphorylation of proteins with molecular masses of 125, 95 and 85 kDa. In contrast, thrombin induced similar phosphorylation patterns to those in controls, a finding that we have also made ( Le Blanc & Samuelsson, 1998). Furthermore, phosphorylation of JAK‐2 and its substrate STAT‐5 was also diminished in all patients that they investigated ( Moliterno et al , 1998 ).…”
Section: Discussionsupporting
confidence: 87%
“…Immunoblots showed a major band around 85 kDa, corresponding to c‐mpl, as well as weaker bands of lower molecular weight, a phenomenon of unknown significance and previously noted with the same antibody (Dr T. Kato, personal communication). In a parallel study of signal transduction in PV platelets, we examined the same samples for the expression of GPIIIa, which was the same in PV and healthy controls ( Le Blanc & Samuelsson, 1998), ensuring that similar amounts of platelet lysate protein was studied in both groups. Of the seven c‐mpl‐positive patients, only two were receiving bone marrow‐suppressive agents (one busulphan and one hydroxyurea), whereas six out of eight c‐mpl‐negative patients were treated with such agents (three hydroxyurea, two anagrelide and one α‐interferon).…”
Section: Resultsmentioning
confidence: 99%
“…Washed, Fg depleted platelets were prepared by repeated centrifugation using a method modified from LeBlanc et al (18). PGE1 (1 µM) and apyrase (1.0 U/ml) were added to the prepared PRP to minimize activation, followed by centrifugation at 1000 g for 10 minutes.…”
Section: Platelet Preparationmentioning
confidence: 99%
“…Together, despite the pronounced elevation of [Ca 2 þ ] i , only select functional platelet responses were observed after stimulation with b-BA. Along these lines it was found that platelets in polycythaemia vera exhibit decreased aggregation after stimulation with PAF, although an equal increase in [Ca 2 þ ] i was seen as compared to platelets from healthy donors (Le Blanc et al, 2000). Also, a patient was described with defective platelet aggregation in response to ionophore A23187, despite normal increases in [Ca 2 þ ] i (Fuse et al, 1999).…”
mentioning
confidence: 94%